Development of a novel damage approach on the microstructure for modeling woven ceramic matrix composites. Issue 1 (18th November 2019) - Reuvers, Marie-Christine; Rezaei, Shahed; Brepols, Tim; Reese, Stefanie
Abstract: Ceramic Matrix Composites (CMC) overcome limitations associated with classical technical ceramics e.g. low fracture toughness and brittle failure under mechanical or thermomechanical loading [1]. Their high temperature stability and low weight makes them attractive for use in various fields, especially aerospace industry, where they improve engine efficiency compared to metal components. However current CMCs lack well established material property design databases for a reliable use in critical aerospace structures. Demonstrating the durability of this relatively new class of materials is the challenge to face and therefore the failure mechanisms need to be investigated further. This contribution deals with the successive development of a woven representative volume element (RVE) for arbitrary CMCs. In contrast to previously developed continuum mechanical or laminate theory based modeling approaches, the introduced model combines various damage formulations. The fiber bridging effect, resulting from the weak interface bond of matrix and reinforcement, is governed by the use of cohesive zone (CZ) elements [2]. Whereas the matrix damage is represented using a continuum mechanical approach [3].